2020
DOI: 10.1111/ane.13338
|View full text |Cite
|
Sign up to set email alerts
|

Severe neurological nicotine intoxication by e‐cigarette liquids: Systematic literature review

Abstract: Electronic cigarettes (e-cigarettes), also named 'e-cig', 'smoke-less-cigarettes' and 'electronic nicotine delivery systems' (ENDS) were developed by a Chinese pharmacist in 2003 and introduced to Western countries in 2004, as a source of nicotine alternative to conventional tobacco products. In recent years, the popularity of e-cigarettes has been increasing among middle and high school students and adults. 1 In fact, e-cigarettes are supposed to have fewer adverse effects on human health than traditional tob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…For ENDS toxicity, we found high-level evidence that most ENDS products contain toxic substances (eg, metals, carcinogens) that are capable of causing DNA damage and mutagenesis, and that ENDS emissions increase airborne toxicants (eg, metals), PM and nicotine in indoor environments compared with background levels 30 32 34 36 51 52. For ENDS health effects, we found high-level evidence that ENDS devices can explode and cause burns, and that intentional or accidental liquid poisoning can cause seizures, anoxic brain injury, or death 62 103 105. We also found high-level evidence that ENDS use exacerbates asthma, and that nicotine in ENDS can cause addiction.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…For ENDS toxicity, we found high-level evidence that most ENDS products contain toxic substances (eg, metals, carcinogens) that are capable of causing DNA damage and mutagenesis, and that ENDS emissions increase airborne toxicants (eg, metals), PM and nicotine in indoor environments compared with background levels 30 32 34 36 51 52. For ENDS health effects, we found high-level evidence that ENDS devices can explode and cause burns, and that intentional or accidental liquid poisoning can cause seizures, anoxic brain injury, or death 62 103 105. We also found high-level evidence that ENDS use exacerbates asthma, and that nicotine in ENDS can cause addiction.…”
Section: Discussionmentioning
confidence: 74%
“…Burn severity was typically second-degree (35%) or second- and third-degree burns (20%) 102. Three reviews reported on poisoning (accidental, intentional) through the ingestion or injection of ENDS liquid 62 103 105. In some cases, patients mixed liquid with alcohol, methadone or benzodiazepines 103.…”
Section: Resultsmentioning
confidence: 99%
“…4 A systematic review of the available literature on e-liquid ingestion revealed that 20/38 (53%) of the patients died before or shortly after hospital admission, primarily due to arrhythmia and cardiac arrest. 5 Our case describes the development of acute brain lesions in different vascular territories following ingestion of refill solution. After exclusion of central nervous system infection, the primary etiological consideration was embolic stroke due to the lesions' distribution, location, and size.…”
Section: Discussionmentioning
confidence: 98%
“…9 In addition to these paediatric cases, there have been 20 adult fatalities following the ingestion or injection of nicotine-containing e-fluids around the world; however, all of these were deemed deliberate attempts at self-harm. 10,11 Non-fatal harm from nicotine-containing e-fluids is also evident with the Victorian Poisons Information Centre receiving 38 calls, January-November 2019, for cases of e-fluid poisoning; 17 of which involved children. 12 Concentrations available for imported pre-mixed efluid bottles already containing nicotine (generally ≤36 mg/mL) are usually fitted with dropper-style dispensers (98% of samples purchased by our laboratory; n = 56), which make rapid delivery of large volumes difficult (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, there has only been one paediatric fatality in the literature involving pre‐mixed low concentration nicotine, where a 15‐month‐old infant in Korea was mistakenly given 5 mL of a 10 mg/mL e‐fluid solution in place of cold medicine 9 . In addition to these paediatric cases, there have been 20 adult fatalities following the ingestion or injection of nicotine‐containing e‐fluids around the world; however, all of these were deemed deliberate attempts at self‐harm 10,11 . Non‐fatal harm from nicotine‐containing e‐fluids is also evident with the Victorian Poisons Information Centre receiving 38 calls, January–November 2019, for cases of e‐fluid poisoning; 17 of which involved children 12…”
Section: Discussionmentioning
confidence: 99%